Mycelial biomass growth stage at death determines fungal necromass decay dynamics - François Maillard; Danny Lopes Ramos; Bowen Zhang; Ashish Ahlawat; Allison L. Gill; Carl Troein; Mattias Hedenström; Tobias Sparrman; Per Persson; Anders Tunlid (Soil Biology and Biochemistry, 2026)

Iron dynamics of boreal lakes inferred from iron speciation analysis of varved lake sediments - Caroline Björnerås; Antti E. K. Ojala; Dan Hammarlund; Per Persson; Emma S. Kritzberg (Journal of Paleolimnology, 2025)
Iron (Fe) concentrations are increasing in lakes on a wide geographical scale, contributing to recent browning of lake waters. As available time series on lake-water Fe concentrations are relatively short, covering the past few decades only, varved lake sediments may provide extended and precisely dated records to study temporal Fe dynamics in lakes in response to environmental drivers, such as changes in catchment land use and atmospheric sulphur deposition. Here, we present and discuss temporal changes in Fe speciation and accumulation rates during the last three centuries as revealed by sub-annually resolved X-ray absorption spectroscopy analyses of varved sediments from three lakes in southern Finland. Iron speciation in sediments is dominated by Fe-bearing silicate fractions in two of the lakes, while the third lake has contributions of organically complexed Fe and Fe-(oxy)hydroxides. Long-term changes in sediment Fe accumulation correspond with documented shifts in land use from agriculture to spruce forestry in the lake catchments, and in one of the lakes with water-level lowering. An overall poor correspondence between monitored aqueous Fe concentrations and sediment-inferred Fe accumulation rates is likely linked to the dominance in the sediments of particulate Fe phases that are not prevalent in suspended form in the water column. This suggests that sediment records are unsuitable for reconstructions of past lake-water Fe concentrations in these lakes. However, the study provides valuable insight into how major land-use changes in the past have affected both the supply and speciation of Fe accumulated in lake sediments.

Minerals, microbes and melanin drive differential incorporation of fungal necromass carbon and nitrogen into mineral-associated organic matter - Katilyn V. Beidler; Elizabeth Huenupi; Lang C. DeLancey; François Maillard; Bowen Zhang; Per Persson; Peter G. Kennedy; Richard Phillips (Soil Biology and Biochemistry, 2025)

Genome-centric metagenomics reveals the effect of organic carbon source on one-stage partial denitrification-anammox in biofilm reactors - Zejia Zheng; David J.I. Gustavsson; Dan Zheng; Felix Holmin; Per Falås; Britt-Marie Wilén; Oskar Modin; Frank Persson (Journal of Environmental Management, 2025)

Visualization of soil aggregate structures provides insights into their formation mechanisms induced by litter inputs - Milda Pucetaite; Per Persson; Julia Parker; Ulf Johansson; Edith C. Hammer (Soil Biology and Biochemistry, 2025)

Reactions between ferric oxyhydroxide mineral coatings and a dimethoxyhydroquinone: A source of hydroxyl radicals - Gry Lyngsie; Simon D. Herzog; Hans Christian Bruun Hansen; Per Persson (Science of The Total Environment, 2024)

Fungal decomposition and transformation of molecular and colloidal fractions of dissolved organic matter extracted from boreal forest soil - Luigi Gentile; Dimitrios Floudas; Ulf Olsson; Per Persson; Anders Tunlid (Soil Biology and Biochemistry, 2024)

Biomass production and fuel characteristics from long rotation poplar plantations - Henrik Böhlenius; Marcus Öhman; Fredrik Granberg; Per-Ove Persson (Biomass and Bioenergy, 2023)

Metagenomic evidence of a novel family of anammox bacteria in a subsea environment - Carolina Suarez; Paula Dalcin Martins; Mike S.M. Jetten; Sabina Karačić; Britt Marie Wilén; Oskar Modin; Per Hagelia; Malte Hermansson; Frank Persson (Environmental Microbiology, 2022)
Summary Bacteria in the order ‘ Candidatus Brocadiales’ within the phylum Planctomycetes ( Planctomycetota ) have the remarkable ability to perform anaerobic ammonium oxidation (anammox). Two families of anammox bacteria with different biogeographical distributions have been reported, marine Ca . Scalinduaceae and freshwater Ca . Brocadiaceae. Here we report evidence of three new species within a novel genus and family of anammox bacteria, which were discovered in biofilms of a subsea road tunnel under a fjord in Norway. In this particular ecosystem, the nitrogen cycle is likely fuelled by ammonia from organic matter degradation in the fjord sediments and the rock mass above the tunnel, resulting in the growth of biofilms where anammox bacteria can thrive under oxygen limitation. We resolved several metagenome‐assembled genomes (MAGs) of anammox bacteria, including three Ca . Brocadiales MAGs that could not be classified at the family level. MAGs of this novel family had all the diagnostic genes for a full anaerobic ammonium oxidation pathway in which nitrite was probably reduced by a NirK‐like reductase. A survey of published molecular data indicated that this new family of anammox bacteria occurs in many marine sediments, where its members presumably would contribute to nitrogen loss.

A widespread mechanism in ectomycorrhizal fungi to access nitrogen from mineral‐associated proteins - Tao Wang; Per Persson; Anders Tunlid (Environmental Microbiology, 2021)
Summary A large fraction of nitrogen (N) in forest soils is present in mineral‐associated proteinaceous compounds. The strong association between proteins and minerals limits microbial accessibility to this source, which is a relatively stable reservoir of soil N. We have shown that the ectomycorrhizal (ECM) fungus Paxillus involutus can acquire N from iron oxide‐associated proteins. Using tightly controlled isotopic, spectroscopic and chromatographic experiments, we demonstrated that the capacity to access N from iron oxide‐associated bovine serum albumin (BSA) is shared with the ECM fungi Hebeloma cylindrosporum and Piloderma olivaceum . Despite differences in evolutionary history, growth rates, exploration types and the decomposition mechanisms of organic matter, their N acquisition mechanisms were similar to those described for P. involutus . The fungi released N from mineral‐associated BSA by direct action of extracellular aspartic proteases on the mineral‐associated BSA, without initial desorption of the protein. Hydrolysis was suppressed by the adsorption of proteases to minerals, but this adverse effect was counteracted by the secretion of compounds that conditioned the mineral surface. These data suggest that the enzymatic exudate‐driven mechanism to access N from mineral‐associated proteins is found in ECM fungi of multiple lineages and exploration types.

ETS and plastid sequence data indicate a spontaneous origin of Scandinavian betony, Betonica officinalis L. - Arne Thell; Mats Hansson; Per-Erik Persson; Mark R. D. Seaward; Maik Veste; Mikael Hedrén (Biologia Futura, 2019)

A model for granite evolution based on non-equilibrium magma separation: evidence from the Gharib and Qattar fluorite-bearing granites, Eastern Desert, Egypt - Anders Lindh; Mohamed A. Abu El-Rus; Mohamed Abdel-Moneim Mohamed; Per-Olof Persson; Anders Scherstén (International Journal of Earth Sciences, 2019)

Subsea tunnel reinforced sprayed concrete subjected to deterioration harbours distinct microbial communities - Sabina Karačić; Britt-Marie Wilén; Carolina Suarez; Per Hagelia; Frank Persson (Biofouling, 2018)

Mineral surface‐reactive metabolites secreted during fungal decomposition contribute to the formation of soil organic matter - Tao Wang; Zhaomo Tian; Per Bengtson; Anders Tunlid; Per Persson (Environmental Microbiology, 2017)
Summary Soil organic matter (SOM) constitutes the largest terrestrial C pool. An emerging, untested, view is that oxidation and depolymerization of SOM by microorganisms promote the formation of SOM‐mineral associations that is critical for SOM stabilization. To test this hypothesis, we performed laboratory‐scale experiments involving one ectomycorrhizal and one saprotrophic fungus that represent the two major functional groups of microbial decomposers in the boreal forest soils. Fungal decomposition enhanced the retention of SOM on goethite, partly because of oxidative modifications of organic matter (OM) by the fungi. Moreover, both fungi secreted substantial amounts (> 10% new biomass C) of aromatic metabolites that also contributed to an enhanced mineral retention of OM. Our study demonstrates that soil fungi can form mineral‐stabilized SOM not only by oxidative conversion of the SOM but also by synthesizing mineral surface‐reactive metabolites. Metabolites produced by fungal decomposers can play a yet overlooked role in the formation and stabilization of SOM.

Chemical changes in organic matter after fungal colonization in a nitrogen fertilized and unfertilized Norway spruce forest - César Nicolás; Juan P. Almeida; Magnus Ellström; Adam Bahr; Sharon E. Bone; Nicholas P. Rosenstock; John R. Bargar; Anders Tunlid; Per Persson; Håkan Wallander (Plant and Soil, 2017)

Six-week follow-up after HIV-1 exposure: a position statement from the Public Health Agency of Sweden and the Swedish Reference Group for Antiviral Therapy - Hans Gaines; Jan Albert; Maria Axelsson; Torsten Berglund; Magnus Gisslén; Anders Sönnerborg; Anders Blaxhult; Gordana Bogdanovic; Maria Brytting; Christina Carlander; Leo Flamholc; Per Follin; et al. (Infectious Diseases, 2016)

The effects of acoustical refurbishment of classrooms on teachers’ perceived noise exposure and noise-related health symptoms - Jesper Kristiansen; Søren Peter Lund; Roger Persson; Rasmus Challi; Janni Moon Lindskov; Per Møberg Nielsen; Per Knudgaard Larsen; Jørn Toftum (International Archives of Occupational and Environmental Health, 2016)

A study of classroom acoustics and school teachers’ noise exposure, voice load and speaking time during teaching, and the effects on vocal and mental fatigue development - Jesper Kristiansen; Søren Peter Lund; Roger Persson; Hitomi Shibuya; Per Møberg Nielsen; Matthias Scholz (International Archives of Occupational and Environmental Health, 2014)

Soil organic phosphorus transformations in a boreal forest chronosequence - Andrea G. Vincent; Johan Vestergren; Gerhard Gröbner; Per Persson; Jürgen Schleucher; Reiner Giesler (Plant and Soil, 2013)

The ectomycorrhizal fungus Paxillus involutus converts organic matter in plant litter using a trimmed brown‐rot mechanism involving Fenton chemistry - Francois Rineau; Doris Roth; Firoz Shah; Mark Smits; Tomas Johansson; Björn Canbäck; Peter Bjarke Olsen; Per Persson; Morten Nedergaard Grell; Erika Lindquist; Igor V. Grigoriev; Lene Lange; et al. (Environmental Microbiology, 2012)
Summary Soils in boreal forests contain large stocks of carbon. Plants are the main source of this carbon through tissue residues and root exudates. A major part of the exudates are allocated to symbiotic ectomycorrhizal fungi. In return, the plant receives nutrients, in particular nitrogen from the mycorrhizal fungi. To capture the nitrogen, the fungi must at least partly disrupt the recalcitrant organic matter–protein complexes within which the nitrogen is embedded. This disruption process is poorly characterized. We used spectroscopic analyses and transcriptome profiling to examine the mechanism by which the ectomycorrhizal fungus Paxillus involutus degrades organic matter when acquiring nitrogen from plant litter. The fungus partially degraded polysaccharides and modified the structure of polyphenols. The observed chemical changes were consistent with a hydroxyl radical attack, involving Fenton chemistry similar to that of brown‐rot fungi. The set of enzymes expressed by Pa. involutus during the degradation of the organic matter was similar to the set of enzymes involved in the oxidative degradation of wood by brown‐rot fungi. However, Pa. involutus lacked transcripts encoding extracellular enzymes needed for metabolizing the released carbon. The saprotrophic activity has been reduced to a radical‐based biodegradation system that can efficiently disrupt the organic matter–protein complexes and thereby mobilize the entrapped nutrients. We suggest that the released carbon then becomes available for further degradation and assimilation by commensal microbes, and that these activities have been lost in ectomycorrhizal fungi as an adaptation to symbiotic growth on host photosynthate. The interdependence of ectomycorrhizal symbionts and saprophytic microbes would provide a key link in the turnover of nutrients and carbon in forest ecosystems.

Effects of 17α-ethinylestradiol on individual life-history parameters and estimated population growth rates of the freshwater gastropods Radix balthica and Bithynia tentaculata - Per Hallgren; Zaoia Sorita; Olof Berglund; Anders Persson (Ecotoxicology, 2012)

Can the job content questionnaire be used to assess structural and organizational properties of the work environment? - Roger Persson; Åse Marie Hansen; Anne Helene Garde; Jesper Kristiansen; Catarina Nordander; Istvan Balogh; Kerstina Ohlsson; Per-Olof Östergren; Palle Ørbæk (International Archives of Occupational and Environmental Health, 2012)

Reconnecting to the Biosphere - Carl Folke; Åsa Jansson; Johan Rockström; Per Olsson; Stephen R. Carpenter; F. Stuart Chapin; Anne-Sophie Crépin; Gretchen Daily; Kjell Danell; Jonas Ebbesson; Thomas Elmqvist; Victor Galaz; et al. (Ambio, 2011)

Heart rate variability changes in physicians working on night call - Birgitta Malmberg; Roger Persson; Per Flisberg; Palle Ørbaek (International Archives of Occupational and Environmental Health, 2011)

Work stress, worries, and pain interact synergistically with modelled traffic noise on cross-sectional associations with self-reported sleep problems - Jesper Kristiansen; Roger Persson; Jonas Björk; Maria Albin; Kristina Jakobsson; Per-Olof Östergren; Jonas Ardö (International Archives of Occupational and Environmental Health, 2011)

Fourier transform infrared spectroscopy, a new method for rapid determination of total organic and inorganic carbon and biogenic silica concentration in lake sediments - Peter Rosén; Hendrik Vogel; Laura Cunningham; Nina Reuss; Daniel J. Conley; Per Persson (Journal of Paleolimnology, 2010)

Space use and territoriality of wolverines (Gulo gulo) in northern Scandinavia - Jens Persson; Per Wedholm; Peter Segerström (European Journal of Wildlife Research, 2010)

Terrestrial organic matter and light penetration: Effects on bacterial and primary production in lakes - Jenny Ask; Jan Karlsson; Lennart Persson; Per Ask; Pär Byström; Mats Jansson (Limnology and Oceanography, 2009)
We investigated productivity at the basal trophic level in 15 unproductive lakes in a gradient ranging from clear‐water to brown‐water (humic) lakes in northern Sweden. Primary production and bacterial production in benthic and pelagic habitats were measured to estimate the variation in energy mobilization from external energy sources (primary production plus bacterial production on allochthonous organic carbon) along the gradient. Clear‐water lakes were dominated by autotrophic energy mobilization in the benthic habitat, whereas humic lakes were dominated by heterotrophic energy mobilization in the pelagic habitat. Whole‐lake (benthic + pelagic) energy mobilization was negatively correlated to the light‐extinction coefficient, which was determined by colored terrestrial organic matter in the lake water. Thus, variation in the concentration of terrestrial organic matter and its light‐absorbing characteristics exerts strong control on the magnitude, as well as on the processes and pathways, of energy mobilization in unproductive lakes. We suggest that unproductive lakes in general are sensitive to input of terrestrial organic matter because of its effects on basal energy mobilization in both benthic and pelagic habitats.

Whole‐lake estimates of carbon flux through algae and bacteria in benthic and pelagic habitats of clear‐water lakes - Jenny Ask; Jan Karlsson; Lennart Persson; Per Ask; Pär Byström; Mats Jansson (Ecology, 2009)
This study quantified new biomass production of algae and bacteria in both benthic and pelagic habitats of clear‐water lakes to contrast how carbon from the atmosphere and terrestrial sources regulates whole‐lake metabolism. We studied four small unproductive lakes in subarctic northern Sweden during one summer season. The production of new biomass in both benthic and pelagic habitats was calculated as the sum of autotrophic production by algae and heterotrophic production by bacteria using allochthonous organic carbon (OC). Whole‐lake production of new biomass was dominated by the benthic habitat (86% ± 4% [mean ± SD]) and by primary production (77% ± 9%). Still, heterotrophic bacteria fueled by allochthonous OC constituted a significant portion of the new biomass production in both benthic (19% ± 11%) and pelagic habitats (51% ± 24%). In addition, overall net production (primary production minus respiration) was close to zero in the benthic habitats but highly negative (−163 ± 81 mg C·m −2 ·d −1 ) in pelagic regions of all lakes. We conclude (1) that allochthonous OC supported a significant part of total production of new biomass in both pelagic and benthic habitats, (2) that benthic habitats dominated the whole‐lake production of new biomass, and (3) that respiration and net CO 2 production dominated the carbon flux of the pelagic habitats and biomass production dominated the benthic carbon flux. Taken together, these findings suggest that previous investigations have greatly underestimated the productivity of clear‐water lakes when benthic autotrophic production and metabolism of allochthonous OC have not been measured.

The role of the amphipod Gammarus locusta as a grazer on macroalgae in Swedish seagrass meadows - Sandra Andersson; Malin Persson; Per-Olav Moksnes; Susanne Baden (Marine Biology, 2009)

Effects of stream predator richness on the prey community and ecosystem attributes - Erika Nilsson; Karin Olsson; Anders Persson; Per Nyström; Gustav Svensson; Ulf Nilsson (Oecologia, 2008)

Fourier transform infrared spectroscopy, a new cost-effective tool for quantitative analysis of biogeochemical properties in long sediment records - Hendrik Vogel; Peter Rosén; Bernd Wagner; Martin Melles; Per Persson (Journal of Paleolimnology, 2008)

Fourier-transform Infrared Spectroscopy (FTIRS), a New Method to Infer Past Changes in Tree-line Position and TOC using Lake Sediment - Peter Rosén; Per Persson (Journal of Paleolimnology, 2006)

Phylogenetic position of Nerillidae and Aberranta (Polychaeta, Annelida), analysed by direct optimization of combined molecular and morphological data - Katrine Worsaae; Arne Nygren; Greg W. Rouse; Gonzalo Giribet; Jenny Persson; Per Sundberg; Fredrik Pleijel (Zoologica Scripta, 2005)
The phylogenetic position of the most speciose meiofaunal polychaete family, Nerillidae, has remained contentious. Recent hypotheses have generally focused on the fact that Nerillidae shares with Aciculata (a major polychaete subgroup) features such as compound chaetae, ventral buccal organ and short ventrolateral palps. Here we present the first phylogenetic analysis of Aciculata, together with Nerillidae, combining morphological and molecular data. We also include Aberrantidae, previously referred to or placed near to spiomorph polychaetes, but recently referred to Aciculata, possibly close to Nerillidae. The data sets of 24 terminals contain 53 morphological characters and nearly complete sequences of 18S rRNA. The sequences were analysed simultaneously with the morphological data by direct optimization in the program POY with a variety of parameter settings (costs of gaps: transversions: transitions). The various settings resulted in markedly different phylogenetic hypotheses, but on the basis of congruence (ILD) the results of two parameter settings were chosen. In all analyses, the three included nerillid species constituted a monophyletic group. Only two analyses provided fully resolved cladograms. The morphological analysis gave poor resolution and the position of the nerillids was equivocal. The two molecular‐based cladograms (minimizing ILD) were also poorly resolved, but one provided a position for nerillids next to Eunice pennata and Nothria conchilega , from the subgroup Eunicida within Aciculata. The two cladograms of the combined analyses (minimizing ILD) were fully resolved and placed nerillids in a terminal position next to Aberranta sp., within a clade of eunicidan species. The study showed that the analytical conditions for the homology assignment of 18S rRNA strongly influenced the phylogenetic results. The various previous proposals on the phylogenetic position of the Nerillidae are reviewed, some of which are in accordance with the results of the present study.

Trends in urinary bladder cancer incidence in Sweden 1960-93 with special reference to histopathology, time period, birth cohort, and smoking - Magnus Thörn; Reinhold Bergström; Anna-Maria Johansson; Lars Ramström; Ingemar Persson; Per-Uno Malmström (Cancer Causes & Control, 1997)

Sediment-chemistry response to land-use change and pollutant loading in a hypertrophic lake, southern Sweden - Siv Olsson; Joachim Regnéll; Anders Persson; Per Sandgren (Journal of Paleolimnology, 1997)